Diagonal torsion matrices associated with modular data - Singh, G. (Algebra and Discrete Mathematics, 2021)
Modular data are commonly studied in mathematics and physics. A modular datum defines a finite-dimensional representation of the modular group SL₂(Z). Cuntz (2007) defined isomorphic integral modular data. Here we discuss isomorphic integral and non-integral modular data as well as non-isomorphic but closely related modular data. In this paper, we give some insights into diagonal torsion matrices associated to modular data.